Community Work: Theories, Experiences & Challenges - Woods, Jennifer (Space and Culture, India, 2014)
Goel, K., Pulla, V. and Francis, A. P. (Eds.), 2014. Bangalore: Niruta Publications, 262 pages, A$29.95, Rs. 350/-